#TITLE_ALTERNATIVE# - PRASETYA NUGROHO (NIM. 18014005), KURNIAWAN
The development of photovoltaic systems requires DC-DC boost converters that have high voltage gain, low input current ripples, and high efficiency in order to serve on-grid installation. In this study, a new simplified multiphase cascaded boost converter (Dahono-8) was proposed to meet these criteria. This converter has the advantage of being able to generate voltage gain ratio without having to operate the duty cycle to the extreme condition. However, the output voltage of the solar panel fluctuates depending on the sunlight intensity that the solar panel received making the output voltage of the converter also change. In addition, the load changes also affect the converter output voltage. So, it needs a voltage control system to regulate the output voltage to remain constant. System control using double loop PI is considered capable of producing a fast and stable system response. To determine the transfer function for control is done by small signal analysis method while to determine the voltage gain equation is used state space averaging method. Verification of the mathematical model is done by simulation and experiment. The data obtained during the research are voltage gain curves and converter stability. The result shows that Dahono-8 boost converter has high voltage gain ratio and control system using double-loop PI able to make the system stable at the desired condition.